الشورى بين الالتزام الإداري و اليقين الإيماني - عقري, الأستاذة: زكية (Sciences de l'Homme et de la Société, 2015)
إن مصادر التشريع الإسلامي الأساسية - متمثلةً في القرآن الكريم والسنة النبوية - مليئةٌ بالمبادئ والقيم والأُطُر والأسس التي تحكم أي فكر إداري متميز، لكن للأسف لم يتوقف أحد بشكل علمي لاستخراج هذه الكنوز، رغم تنوعها وشمولها، فالإدارة من العلوم الاجتماعية التي تتناول السلوك الإنساني. وفي هذا المقال نحاول الوقوف على مبدأ عظيم من مبادئ الإدارة والتنظيم، وركن ركين من أركان القيادة الفعّالة كما صورها القرآن الكريم، وهو مبدأ الشورى كمطلب وضرورة إدارية، وكقيمة إيمانية حقيقية تنشأ مع الفرد والجماعة في كل ممارساتهم الحياتية. Abstract : The fundamental sources of Islamic law - represented in the Koran and sunnah- are full of principles, values and concepts that govern all thoughts and administrative ideas, but unfortunately no one tried scientifically to extract these riches, despite their diversity. In this article, we try to keep a key principle of management and organization and one of the important pillars of effective command as described by the Qur'an which is the principle of "Shura" as a requirement and an administrative necessity and also as an actual value of the faith that comes with the individual and the group in all their participles of life.